Students’ insights on taking four english subjects in the journalism major at the journalism department, School of arts and social sciences, University of El Salvador, year 2015 - Morales Abarca, Blanca Dinora
Learning English as a Foreign Language has become an essential part on the resume of any professional. The School of Sciences and Humanities at the Foreign Language Department in the University of El Salvador offers a variety of Majors (to take a subject as the main part of one’s study at college or University) in which it is essential to take English as a requirement to graduate. As an example, in the Journalism Major at the Journalism Department, students take four different courses of Intensive English as part of their program. This situation could be perceived as a barrier for these students because taking English as a part of their academic charge can imply to take more time in their career if they fail any of the 4 English courses. It is for that reason that there is an interest in making a study in which the students’ personal, academic and social insights about taking four English in the Journalism Major at the Journalism Department are going to be researched. Managing English as a foreign language is a characteristic that helps professionals to get a better job position and also to enrich the amount of opportunities regarding personal and professional growing. Nowadays in our society, the demand of learning English generally encourages individuals to focus their educational requirements primarily on become fluent in this language. According to Robert Pinon and Jhon Haydon education is driven by a number of factors around the world as in many countries such as Cameroon, Nigeria, Rwanda, Bangladesh and Pakistan. These include inward investment (with international companies typically using English for internal communication), ambitious individuals looking to sharpen their competitive edge in the labor market, as well as government efforts to encourage business investment by allocating greater budgets to the teaching of English. A custom report compiled by Euromonitor International for the British Council (December 2010). The Benefits of the English Language for Individuals and Societies: Quantitative Indicators. London, London: Euromonitor International. Based on this affirmation it is relevant to mention that in the majority of countries where English is being taught, it is noticeable the improvement of the economical, social and individual margin. Companies that request English to apply for a job position in El Salvador are increasing considerably; it is for that reason that if someone wants to apply for a job position outside the country, the demand of English as part of the resume becomes more than essential.